Some Grain Properties of IR36-Based Starch Mutants - Juliano, Bienvenido O.; Perez, C.M.; Kaushik, R.; Khush, G.S. (Wiley, 1990)
Some grain properties of 20 starch mutants that were transferred from mutants of Japanese rices to IR36 (by two backcrosses to IR36) were studied. All had higher apparent amylose content (AC) and gelatinization temperature (GT) than the parent mutants, except the dull mutants, and the 82GF sugary mutant which had no amylose. All had lighter and lower density brown rices than IR36. Sugary 82GF und EM5 had high free sugars, and sugary and EM20 shrunken‐1 had high fat content. Phytoglycogen content of brown rice was 34% for 82GF and 7% for EM5 sugary mutants. Amylose extender mutants had higher lysine in brown rice protein than IR36 parent. Alkali spreading value did not accurately estimate GT of these starch mutants. Milled rice of the two high amylose extender mutants 2064 and EM16 had lower Amylograph peak viscosity but higher cooked rice Instron hardness than IR36 milled rice.